2007
DOI: 10.1249/01.mss.0000246989.48729.39
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Strength Training of the Legs in COPD

Abstract: In combination with the observed improvement in FEV1, these data certainly support the therapeutic role for MST in the treatment of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 31 publications
8
64
1
Order By: Relevance
“…A high rate of torque development has been suggested to relate to an individual’s ability to perform functionally at faster contraction speeds 32,33. Our findings support the relationship between rate of torque development and performance of all three functional tests in patients with COPD.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A high rate of torque development has been suggested to relate to an individual’s ability to perform functionally at faster contraction speeds 32,33. Our findings support the relationship between rate of torque development and performance of all three functional tests in patients with COPD.…”
Section: Discussionsupporting
confidence: 86%
“…Contrary to our expectations, however, high-velocity concentric contractions were not as strongly associated with functional or physiological performance as were slower-velocity concentric and eccentric contractions. There is some evidence in healthy adults that adequate functional performance is determined by fast-velocity contractions,31 and using fast-velocity (power) exercise during training results in greater functional performance compared with slow-velocity training 32,33. It is not apparent why these results are contradictory; however, because patients with COPD exhibit significant deficiencies in functional performance6 and typically do not produce fast contractions in their daily life, it is possible that high-velocity torque production using an isokinetic dynamometer was extremely unfamiliar.…”
Section: Discussionmentioning
confidence: 99%
“…Plantar Xexion force and EMG were analysed using MegaWin software (Mega Electronics LTD, Kuopio, Finland). Dynamic RFD (N s ¡1 ) was calculated from the 10-90% of peak force in the concentric phase of the lift (HoV et al 2007) and analysed using Bioware v3.06b software (Kistler, Switzerland). The plantar Xexion force was multiplied with the consistent moment arm length of 0.15 m (measured from the heel block to the centre of the force transducer) to attain torque.…”
Section: Electromyography and Force Recordingsmentioning
confidence: 99%
“…The emphasis was put on lowering the weight in a controlled manner until the knee joints were at 90°, short stop (»0.5 s) and then maximal mobilisation of force in the concentric movement with the movement ending in a plantar Xexion. This is a common type of training exercise in our laboratory (HoV et al 2007;Storen et al 2008). The training load corresponded to 85-90% of 1RM, and to stay within this range it was increased by 5-10 kg when the target repetitions could be completed for all sets.…”
Section: Training Interventionmentioning
confidence: 99%
“…No authors reported adverse effects of the training despite some interventions being of a high intensity (≥85% of 1RM). Improvements in maximal tidal volume and FEV1 in the studies by Clark et al 8 and Hof et al 24 respectively, were the only documented changes in pulmonary function parameters. Although FEV1 is important in the diagnosis of COPD, it cannot be reliably correlated with exercise capacity, dsypnea or HRQL.…”
Section: Pulmonary Rehabilitation Immobilitymentioning
confidence: 91%